Biochemical assessment of risk factors in coronary artery disease patients: An observational study in suburban hospital of Hapur, Uttar Pradesh - Sinha, Vivek; Kachhawa, Poonam (Asian Journal of Medical Sciences, 2019)
Background: Coronary risk factors such as hypertension, diabetes and coronary artery disease (CAD) have become major health problem in Indian subcontinent, despite low fat intake and low rates of obesity. It is a paradox that the increased risk of people of Indian origin to diabetes and CAD is not explained by conventional risk factors. It is possible that the presence of new risk factors may explain this paradox. Aims and Objective: The present study was undertaken to estimate the prevalence of coronary artery disease and identify & compare some socio-demographic and lifestyle risk factors associated with coronary artery disease in urban and rural populations of Hapur. Materials and Methods: It’s a community based study in which 350 adults each were randomly selected from urban and rural populations of Hapur using modified cluster sampling method. Selected individuals were examined. Data entry and analysis was done using SPSSversion16 for windows version 8.1. Several published epidemiological and case-controlled studies are reviewed. The prevalence of hypertension (3.2%), diabetes (2.6%) and CAD (3.2%) is very low in the rural population of India. However, in urban and immigrant populations, the prevalence of hypertension (≥160/95, 12–20%), diabetes (6–8%) and CAD (7–14%) is significantly higher than in the developed countries. Result: Out of 350 patients of CAD included in study, 133(38%) were females and 217(62%) were males. Among those 54(15.4%) were below 45 years of age and 296(84.6%) were equal to and above 45 years of age. Risk factors like gender prevalence, family history of IHD, lifestyle, triglycerides level, HDL level, BMI and smoking were not significantly associated with different age groups(p-value >0.05). While HTN, DM, stress, LDL level and cholesterol were found to be significantly associated with age ≥45 years. Conclusions: These studies support the consensus that people of urban origin wherever they are settled should have lower desirable limits of serum cholesterol, body mass index and dietary fat intake and should also decrease new risk factors for prevention of CAD. This finding may require modification of the existing guidelines of the International Task Force for Prevention of CAD.